The Jossey-Bass reader on educational leadership - Jossey-Bass Inc. (San Francisco : Jossey-Bass, 2000)
"Filled with critical insights from best-selling authors and expert practitioners, this unique anthology presents important articles, seminal reports, and book excerpts defining the field of educational leadership today. From building character to building community, this volume is the perfect primer for the aspiring leader - and an indispensable companion for those already in the educational trenches."--Jacket.
-- Leadership, management, and organizational behavior. The nature of leadership / John W. Gardner -- "Give me a lever long enough ... and single-handed I can move the world" / Peter M. Senge -- Condensation of the fourteen points for management / W. Edwards Deming -- We need noncoercive lead-management from the state superintendent to the teacher / William Glasser -- Leadership as an organizational quality / Rodney T. Ogawa and Steven T. Bossert -- People and organizations / Lee G. Bolman and Terrence E. Deal -- Principals and superintendents. Looking for leaders / Susan Moore Johnson -- Standards for school leaders / Interstate School Leaders Licensure Consortium -- The unheroic side of leadership: notes from the swamp / Jerome T. Murphy -- Educational leadership for the twenty-first century: integrating three essential perspectives / David D. Marsh -- Learning to lead / Roland S. Barth -- Leadership for the twenty-first century: breaking the bonds of dependency / Michael Fullan -- The manager as politician / Lee G. Bolman and Terrence E. Deal -- Leading a school system through change / Phillip C. Schlechty -- Eight roles of symbolic leaders / Terrence E. Deal and Kent D. Peterson -- Diversity and leadership. Gender and race as factors in educational leadership and administration / Cherry A. McGee Banks -- Gender and supervision / Charol Shakeshaft, Irene Nowell, and Andy Perry -- Moral leadership. Leadership as stewardship: "Who's serving who?" / Thomas J. Sergiovanni -- The authentic leader / Robert Evans -- Building a community of virtue / Kevin Ryan and Karen E. Bohlin -- Shared leadership. Good-bye, command and control / Margaret Wheatley -- Teacher leadership: ideology and practice / Ann Lieberman, Ellen R. Saxl, and Matthew B. Miles -- Principals, shared decision making, and school reform / Carol H. Weiss and Joseph Cambone -- Assessing the prospects for teacher leadership / Judith Warren Little.
Includes bibliographical references.
Keywords: Educational leadership -- United States; School management and organization -- United States